2013
DOI: 10.7314/apjcp.2013.14.4.2317
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Transtheoretical Model in Predicting Smoking Relapse among Malaysian Adult Smokers Receiving Assistance in Quitting

Abstract: The role of The Transtheoretical Model (TTM) in predicting relapse is limited. We aimed to assess whether this model can be utilised to predict relapse during the action stage. The participants included 120 smokers who had abstained from smoking for at least 24 hours following two Malaysian universities' smoking cessation programme. The smokers who relapsed perceived significantly greater advantages related to smoking and increasing doubt in their ability to quit. In contrast, former smokers with greater self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In Malaysia, the TTM has been translated and validated to be used for the cessation of smoking [16,17]. The TTM application in Malaysia has also been studied for the reduction of body weight [18] and physical activity levels in women [19].…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, the TTM has been translated and validated to be used for the cessation of smoking [16,17]. The TTM application in Malaysia has also been studied for the reduction of body weight [18] and physical activity levels in women [19].…”
Section: Introductionmentioning
confidence: 99%
“…Van et al 35 reported a significant correlation between smokers' social environment and successful SC. Workplace SC programs can assist smokers with lower QS motivation levels to QS and prevent relapses 36 . Therefore, tobacco control campaigns in public places and the creation of supportive SC environments are crucial for people who are ready to QS.…”
Section: Reasons For Quitting Smoking Vary In the Likelihood Of Sc Su...mentioning
confidence: 99%
“…There have been a number of studies carried out in which the distribution of stages for a precise determination of behaviours with increased risk such as smoking was first established [99,100,101,102,103,104]. Researchers were also interested in determining the systematic relationships between the stage the individual was in and the processes of change which they were subjected to [86,87].…”
Section: Studies That Have Shown the Positive Effects Of Using The Trmentioning
confidence: 99%